Study of some mechanical properties of low carbon steel dipped in (Al-14 Wt %Si) liquid alloy - Aldaghari, Khalifa. S.; Aldullmey, Abbas. A. (Al-Mukhtar Journal of Sciences, 2010)
Adhesive wear of low carbon steel dipped in Liquid alloy of ( Al-14Wt%Si) at(993 K) for interval times (3,6,9 and12) minutes and air cooling has been investigated under dry sliding conditions. It has been found of increasing of dipping times , reduce the wear rate and improve the adhesive resistance compared with samples with out dipping.